Structural design and safety performance of a novel high-strength steel lightweight guardrail - Hongliang Wei; Yongke Wei; Zhenhua Dai; Tingquan He; Changsong Wu; Dongmin Peng; Feng Zhang (PLoS ONE, 2025)
Highway guardrails are critical safety infrastructure along roadways, designed to redirect vehicles back into their lanes and facilitate a gradual deceleration to a complete stop. Traditional highway steel guardrails exhibit significant limitations, including inadequate energy absorption, susceptibility to corrosion, and an increased risk of vehicles leaving the roadway during severe collisions. Furthermore, the production and transportation of these guardrails contribute to substantial carbon emissions and environmental pollution. This study presents an optimization of the cross-sectional shape of the conventional corrugated beam guardrail, proposing a lightweight structure that incorporates high yield strength steel plate HR700F to enhance energy absorption capacity. The safety performance of the proposed guardrail is rigorously assessed through finite element numerical simulations and full-scale collision tests with real vehicles. Key performance indicators—such as the maximum dynamic lateral deflection of the guardrail, occupant impact velocity, and acceleration—are utilized to evaluate the energy absorption and protective efficacy of the structure. Results indicate that the optimized guardrail not only meets SB-level safety standards but also demonstrates superior anti-collision performance and effective energy absorption and buffering characteristics. The proposed design achieves a reduction in beam plate thickness by 1.3 mm, resulting in a lightweight structure with a weight reduction of up to 44%, thereby supporting the advancement of low-carbon, environmentally sustainable transportation solutions.